Oslovení nových zákazníků na B2B trhu ve Velké Británii - Štěrbová, Michaela (Vysoké učení technické v Brně. Fakulta podnikatelská, 2020)
Tato diplomová práce je zaměřena na komunikační mix v české společnosti působící v oblasti webové analytiky a také na jeho návrh pro B2B trh v Anglii. Teoretická část je zaměřena na definici marketingu, mezinárodního marketingu, marketingového a komunikačního mixu. Analytická část je zaměřena na charakteristiku společnosti, analýzu mikro a makro prostředí, analýzu marketingového a komunikačního mixu společnosti. Poslední část je věnována návrhům komunikačního mixu společnosti pro B2B trh v Anglii. Tyto návrhy by měli vést k oslovení nových zákazníků a možnému získání nových zákazníku z již zmiňovaného trhu.

This diploma thesis is focused on the communication mix in a Czech company operating in the field of web analytics and also on its proposed design for the B2B market in England. The theoretical part is focused on the definition of marketing, international marketing, marketing and communication mix. The analytical part is focused on the characteristics of the company, analysis of the micro and macro environment, analysis of the marketing and communication mix of the company. The last part is devoted to the design of the company's communication mix for the B2B market in England. These proposals should lead to reaching new customers and possible gaining of new customers from the already mentioned market.
Reaching new costumers on a B2B market in UK
Keywords: mezinárodní marketing; marketing; marketingový mix; komunikační mix; webová analytika; international marketing; marketing; marketing mix; communication; web analytics